Relationship Between Signal Changes on T2-weighted Magnetic Resonance Images and Cervical Dynamics in Cervical Spondylotic Myelopathy. Issue 6 (July 2015) - Yu, Lipeng; Zhang, Zitao; Ding, Qingfeng; Li, Yiming; Liu, Yuwen; Yin, Guoyong
Abstract : Study Design: Technical note. Objective: To determine the correlation between the high-intensity lesions observed on T2-weighted magnetic resonance images (T2W MRI) and the cervical dynamic characteristics of patients with cervical spondylotic myelopathy (CSM). Summary of Background Data: Intramedullary high signal intensity is frequently observed on T2W MRI of CSM patients and represents pathologic changes in the spinal cord. However, few studies have attempted to identify the effects on cervical dynamics associated with such changes in MRI signals. Methods: This study included 71 CSM patients who were admitted to our hospital between May, 2009 and May, 2012 (44 men, 27 women; average age, 52.5±11.7 y). They were divided into 3 groups depending on T2W MRI data: group 1, no hyperintensity; group 2, slight hyperintensity; and group 3, bright hyperintensity. The Cobb angle on cervical flexion-extension radiographs was measured as a parameter of cervical spine dynamics. Results: Total hyperflexion, hyperextension curvature, range of movement (ROM), and segmental hyperflexion curvature did not differ among the groups ( P >0.05). Segmental hyperextension curvature and ROM were greater in groups 2 and 3 than in group 1 ( P <0.05) but did not differ significantly between groups 2 and 3 ( P >0.05). Conclusions: Increased segmental hyperextension curvature (≥10 degrees) and ROM are risk factors for high-intensity lesions on T2W MRI in CSM patients.